The Activity of Aquatic Extract of Ziziphus Spina-christi against Bacteria, an in Vitro Study - Hadi Jebur, Mays; Khazal Kadhim Hind, Nada; Jassim Hamza, Hiba; F. Alkaim, Ayad (International Journal of Psychosocial Rehabilitation, 2020)
Background: Medicinal plants such as Ziziphus spina-christi were described as one plant in which one of its parts contains compounds that are used for chemotherapeutic purposes or medical crude for the synthesis of useful drugs. So this use of plants in treating ailments has been in practice since a long time ago. Aims: The present paper aimed to evaluate the antibacterial activity of (leaves, stem bark and the combination of leaves + stem bark) aqueous extracts of Z. spina–Christi .in vitro Methods: Antibacterial effects of aquatic leaves, aquatic stem bark, and a combination of leaves and stem bark extracts against five Gram-positive and eight Gram-negative bacteria-—including Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes, Staphylococcus saprophyticus, Streptococcus pneumoniae, Pseudomonas aeruginosa, Enterobacter sp., Klebsiella pneumoniae, Escherichia coli, Salmonella typhi, Proteus mirabilis, Serratia marcescens, and Acinetobacter. Results: Antibacterial activity of these extracts by the well-diffusion method was measured by inhibition zones of five Gram-positive and eight Gram-negative pathogenic microbes. All organisms of this study were highly sensitive to a combination of leaves + stem bark extract, then stem bark aqueous extract; finally, all tested organisms showed slight sensitivity to leaves aqueous extract. Conclusion: Sidir aquatic extracts (leaves, stem bark, and a combination of leaves + stem bark) had an inhibitory effect against all tested bacterial species. This plant also needs further work to discover new broad-spectrum bioactive compounds.